O infinito e sua constituição histórico-filosófica na ciência matemática - Novaes, Karina Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work aimed to develop an exploratory study on the constitution of the concept of finite and infinite in the historical-philosophical process of Mathematics. It is justified by the importance of this concept, mainly in its potential and actual characteristics and because this is an integral part of many mathematical aspects, mainly in the scope of the Differential and Integral Calculus and Mathematical Analysis disciplines. From this, we set out to study some academic works, which point to difficulties in the teaching and learning of Calculus and to an epistemological difficulty in the search for understanding in this discipline, with infinity being one of the agents of these difficulties. The result is a text that presents an understanding about the construction of the concept of finite and infinite in Mathematics, starting from the historical and philosophical structure that enters in this science. We have therefore covered from the cradle of society in Ancient Greece, where the infinite possessed philosophical meaning, up to the contemporary age, in which infinity is a structuring idea of Mathematics and, consequently, of Differential and Integral Calculus itself

Este trabalho teve como objetivo desenvolver um estudo exploratório sobre a constituição do conceito de finito e infinito no processo histórico-filosófico da Matemática. Justifica-se pela importância desse conceito, principalmente em suas características potencial e atual e por este ser parte integrante de muitos aspectos matemáticos, principalmente no âmbito das disciplinas Cálculo Diferencial e Integral e Análise Matemática. Partindo disso, nos propusemos ao estudo de alguns trabalhos acadêmicos, que apontam para dificuldades no ensino e na aprendizagem do Cálculo e para uma dificuldade epistemológica na busca pelo entendimento nessa disciplina, sendo o infinito um dos agentes dessas dificuldades. O resultado é um texto que apresenta uma compreensão acerca da construção do conceito de finito e infinito na Matemática, partindo da estrutura histórica e filosófica que adentra nesta ciência. Por isso, abrangemos desde o berço da sociedade, na Grécia Antiga, onde o infinito possuía significado filosófico, até a era contemporânea, na qual o infinito é uma ideia estruturadora da Matemática e, por consequência, do próprio Cálculo Diferencial e Integral
Infinity and its historical-philosophical constitution in mathematical science
Keywords: Matemática - Estudo e ensino; Infinito; Cálculo diferencial; Mathematics Study and teaching